Cold Disinfestation for 'Red Globe' Grape (Rhamnales: Vitaceae) Infested With Drosophila suzukii (Diptera: Drosophilidae). Issue 3 (1st June 2020) - Wang, Xiaoxue; Zhan, Guoping; Ren, Lili; Sun, Shuangyan; Dang, Haiyan; Zhai, Yifan; Yin, Hong; Li, Zhihong; Liu, Bo
Abstract: The spotted wing drosophila, Drosophila suzukii Matsumura, which is widely spread in the main soft-skinned fruits production areas in China, presents a threat to importing countries. In order to develop a phytosanitary cold treatment measure for preventing the movement of this drosophila fly, cold tolerance of six immature life stages of D. suzukii was compared followed by time-mortality and large-scale confirmatory tests on the most tolerant stage in grape fruit. Egg was defined as the most cold-tolerant stage by comparing the mortality of all the immature stages (egg, first, second, and third instars, early and late pupa) treated at 0 and 2°C. The minimal lethal time (LT) for 99.9968% mortality (95% confidence level [CL]) estimated by the probit model was 10.47 d at 0°C and 11.92 d at 2°C, respectively. Hence, 11 d (at 0°C) and 12 d (at 2°C) were chosen as the target time to conduct the confirmatory tests. No survivors were found among the estimated 50, 385 and 57, 366 treated eggs, which resulted in the efficacy of 99.9941 and 99.9948% mortality (95% CL) at 0 and 2°C, respectively. Our study suggests a technical basis for cold disinfestation on D. suzukii in cage-infested Chinese 'Red Globe' ( Vitis vinifera L.) grape, which could provide flexible phytosanitary treatment for control of D. suzukii in the international trade of grape.